Philippine independence motives, problems, and prospects - Kirk, Grayson L. ([S.l.] [s.n.], 1936)
"THIS little book has been planned as a case study in the motivation of contemporary national policy. In setting forth this account of the forces which were responsible for the Philippine independence act and in estimating the prospects which it provides for our Malay wards, I have made no effort to conceal my own belief that the fundamental problem is yet to be solved. I hope that this modest contribution may aid to some extent in clarifying the issues which surround it."--Preface.
Philippine independence: motives, problems, and prospects -- Preface -- Contents -- I. Assuming the white man's burden -- II. The old independence movement -- III. Trade follows the flag -- IV. The farm groups take a hand -- V. The triumph in Congress -- VI. The economic outlook -- VII. The new constitution, and the political outlook -- VIII. The Japanese problem -- IX. Filipino-American relations: suggested program -- Appendix I. President Hoover's veto message -- Appendix II. The Tydings-MC Duffie Act -- Appendix III. Constitution of the Philippines -- Index.
Includes bibliographical references and index.
Electronic reproduction.